A novel HLA allele, HLA‐B*40:227, was identified by polymerase chain reaction sequence‐based typing in a Chinese individual. Issue 3 (19th August 2013) - Wang, W.; He, J.; Zhang, W.; Zhu, F.‐M.; Lv, H.‐J.
<x xml:space="preserve">Abstract</x> HLA‐B*40:227 has one nucleotide change from B*40:01:01 in exon 2 at position 265 C>G.